PERLINDUNGAN HUKUM PEMEGANG POLIS BUMIPUTERA TERHADAP PEMOTONGAN 50% KLAIM SETELAH BERAKHIRNYA KONTRAK - Richard, Frengky (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
AJB Bumiputera 1912, as the only mutual insurance company in Indonesia, has experienced prolonged liquidity pressure from 2019 to 2025, resulting in defaults on claim settlements to policyholders upon policy maturity. To overcome liquidity problems, the management of AJB Bumiputera 1912 implemented a Benefit Value Reduction (BVR) by cutting premium values of expired contracts by up to 50%, reasoning that policyholders are members obligated to bear company losses in accordance with the company's Articles of Association. This research aims to examine the membership status of policyholders who have filed insurance claims due to contract expiration. This study employs a normative legal research method with a library research approach. The research findings indicate that not all policyholders at AJB Bumiputera 1912 can be burdened with bearing company losses, as long as the policyholders have met the requirements stipulated in Article 56 paragraph (3) of Law Number 4 of 2023 concerning Development and Strengthening of the Financial Sector. Keywords: Insurance, Benefit Value Reduction, Bumiputera